RESEARCH INTO THE POSSIBILITY OF CREATING A WI-FI RADAR FOR DETECTING MOVING FLYING TARGETS IN THE NEARBY AREA OF PROTECTED OBJECTS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
Nowadays, there are much researches on the creation of passive coherent radar systems for detecting aircraft in the airspace. One of them is the use of systems based on Wi Fi signals for detecting a moving target. This paper research the possibility of detecting and determining the parameters of flying targets using Wi Fi radar in nearby area of protected objects. An analysis of the potential capabilities of such a system has been carried out. The conclusion is that the development of such a system is possible for close distances to the protected object.